3.4 A PRESSURE-INDEPENDENT ARTERIAL REMODELLING AND AORTA DILATATION IN TREATED PATIENTS WITH FABRY DISEASE - C. Collin; M. Bensalah; H. Beaussier; D.P. Germain; E. Bozec; E. Mousseaux; S. Laurent; P. Boutouyrie (Artery Research, 2009)
Purpose: Fabry disease is a deficiency of lysosomal enzyme α-galactosidase A leading to accumulation of glycosphyngolipids in cardiac and vascular tissues. After long-term enzyme replacement treatment, we described a continuous vascular hypertrophy whereas the aortic stiffness was paradoxically decreasing. Preliminary results reported aorta dilatation in treated patients. The objective of this study was to determine the prevalence of aortic dilatation, and the relationship between aorta dilatation, aortic stiffness and arterial remodeling in treated Fabry patients. Methods: Case-control study in 34 Fabry males patients (38±12 yrs) receiving enzyme infusions every other week (3.5±1.5 yrs), age-matched with 34 controls. All patients and subjects had arterial measurements of a) carotid IMT and diameter, pulse pressure (PP) and stiffness obtained with echotracking; b) aortic stiffness obtained through carotid-femoral PWV and c) aorta diameters (sinus, ascending and descending tubule, arch aortic) assessed by MRI examinations. Results: Aorta root dilatation (>40mm at sinus) was observed in 13 FD patients (35%), but not at others segments. In controls, sinus diameter was positively correlated with age, aortic and carotid stiffness in univariate analysis (R=0.59, P<0.005; R=0.53, P<0.005 and R=0.68, P>0.0001 respectively) and with both age and CPP in multivariate analysis (R=0.59, P<0.005; R=0.53, P<0.005, respectively).No relationship in Fabry patients were found in the same univariate and multivariate analysis. Carotid IMT is positively correlated with PP in controls, but not in Fabry patients. Conclusion: This study highlight the pressure-independent arterial hypertrophy and aorta dilatation in treated Fabry patients.